A Quest for Meaning: Facing Uncertainty, Anonymity, the Hidden and the Unknown Space in Azeroth - Platell, Annabelle Norma Marye (Curtin University, 2019)
In this thesis I aim to explore how meaning is interpreted and adapted in relation to social performances and the emergence of blind spots. In World of Warcraft, blind spots take the forms of anonymity of players, uncertainty of meaning, venturing through the unknown space, and the hidden. Blind spots form types of knowledge that cannot be ascertained easily or at all while playing. However by identifying them, one can study how meaning is created.